(untitled) (Global Journal of Human-Social Science, 2024)
The peculiarities of the political perception of the phenomenon of blooming complexity are analyzed which is actualized in the theory of the processuality of natural development in the teachings of K Leontiev An attempt is made to conceptualize the political foundations of the blooming complexity phenomenon The basic scientific problem is the identification of characteristic features of the second phase - blooming complexity which fits into the triadic system of the birth establishment and decline of states and civilizations in the theory of K Leontiev The results of the study are representative of the characteristics of the political features of each period of the system primary simplicity flourishing complexity secondary confusing simplification - which appear in homologous unity and historically encapsulate a certain state-civilization in the general historical context The concept of blooming complexity was scientifically reflected upon in the process of consideration of which the ideas of the immanent despotic idea of the state the concept of the real forces of society the vision of K Leontiev regarding the concepts of nation nationalism nationality politics of foundations etc were articulated and worked out as well as the peculiarities of the imperative of the social stratification A political revision of the historiosophical theory of development was carried out according to which a certain state-civilization passing through a three-phase process is replaced by another During the disclosure of the research topic the principles of objectivity and impartiality were used as well as the elimination of subjective evaluative judgments